2016
DOI: 10.1021/acschemneuro.6b00210
|View full text |Cite
|
Sign up to set email alerts
|

Medullary Norepinephrine Projections Release Norepinephrine into the Contralateral Bed Nucleus of the Stria Terminalis

Abstract: Central norepinephrine signaling influences a wide range of behavioral and physiological processes, and the ventral bed nucleus of the stria terminalis (vBNST) receives some of the densest norepinephrine innervation in the brain. Previous work describes norepinephrine neurons as projecting primarily unilaterally; however, recent evidence for cross-hemispheric catecholamine signaling challenges this idea. Here, we use fast-scan cyclic voltammetry and retrograde tracing to characterize cross-hemispheric norepine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
2
7
0
Order By: Relevance
“…In fact, pharmacological analysis revealed that LC stimulation selectively induces NE release in these terminals. NE was released in a frequency-dependent manner at the concentration range that was previously found in other NE terminals following LC stimulation (Fox, Bucher, Johnson, & Wightman, 2016;Herr et al, 2012;Park, Kile, & Wightman, 2009;Park et al, 2017).…”
supporting
confidence: 58%
“…In fact, pharmacological analysis revealed that LC stimulation selectively induces NE release in these terminals. NE was released in a frequency-dependent manner at the concentration range that was previously found in other NE terminals following LC stimulation (Fox, Bucher, Johnson, & Wightman, 2016;Herr et al, 2012;Park, Kile, & Wightman, 2009;Park et al, 2017).…”
supporting
confidence: 58%
“…Fox et al, 2016;Deal et al, 2019), our results for the first time demonstrate the possibility to measure real-time NE efflux in the BLA. Based on pharmacological characterizations, we ruled out the involvement of DA efflux in the signal measured in naïve rats as previously reported for the prefrontal cortex and bed nucleus of the stria terminals (Park et al, 2011;Fox et al, 2016;Deal et al, 2019). As expected, the electrically-evoked NE release was frequency-dependent, while the average maximum concentrations were ∼2-3 fold lower than concentrations in the prefrontal cortex (Deal et al, 2019).…”
Section: Discussionmentioning
confidence: 58%
“…of saline, raclopride (dopamine D 2 receptor antagonist; 2 mg/kg), idazoxan (α 2 adrenergic receptor antagonist; 5 mg/kg), or alcohol (2 g/kg ethanol) was administered. These idazoxan and raclopride doses effectively increase an electrically-evoked catecholamine efflux clarifying whether DA (raclopride) or NE (idazoxan) is detected in the rat brain with FSCV (Park et al, 2015;Fox et al, 2016;Mikhailova et al, 2019;Deal et al, 2018;. Some rats received more than one drug during the FSCV experiment.…”
Section: Fast-scan Cyclic Voltammetrymentioning
confidence: 86%
See 1 more Smart Citation
“…The BNST is a common node in the circuitry underlying stress-induced and anxiety-like behavior [ 6 ]. Noradrenergic neurons in the locus coeruleus and A1/A2 nucleus of the medulla innervate the BNST via the dorsal and ventral noradrenergic bundles, respectively, although the ventral bundle is the dominant source of NE within the region [ 3 , 7 ]. Pharmacological disruption of NE signaling in the BNST prevents stress-induced reinstatement of cocaine-seeking behavior, an animal model of relapse [ 2 , 3 , 6 ].…”
mentioning
confidence: 99%